2021
DOI: 10.1021/acsomega.1c04320
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-Hepatitis B Virus Activity of Euphorbia schimperi and Its Quercetin and Kaempferol Derivatives

Abstract: Natural or plant products, because of their structural diversity, are a potential source for identifying new anti-hepatitis B virus (HBV) agents. Here, we report the anti-HBV activity of Euphorbia schimperi and its quercetin (QRC) and kaempferol derivatives. The anti-HBV-active methanol fraction of E. schimperi was subjected to chromatographic techniques, leading to isolation of three flavonols, following their structure determination by 1 H and 13 C NMR spectroscopies. Their cytotoxicity and anti-HBV potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 56 publications
(110 reference statements)
0
20
0
Order By: Relevance
“…In previous studies, while sea buckthorn leaf extract was reported for anti-DNV activity (32), the isolated compound, hiporamin, was found to exert potent antiviral effects against influenza virus, HSV and HIV (34). Of the three antiviral flavonoids identified in its leaves (34), quercetin and kaempferol, as well as their derivatives have been demonstrated to have marked HBsAg and HBeAg inhibitory potentials in HepG2.2.15 cells (27)(28)(29)(30). Notably, although the broad antiviral potential of isorhamnetin remains unexplored, a previous study reported its in vitro activity against the influenza virus (37).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In previous studies, while sea buckthorn leaf extract was reported for anti-DNV activity (32), the isolated compound, hiporamin, was found to exert potent antiviral effects against influenza virus, HSV and HIV (34). Of the three antiviral flavonoids identified in its leaves (34), quercetin and kaempferol, as well as their derivatives have been demonstrated to have marked HBsAg and HBeAg inhibitory potentials in HepG2.2.15 cells (27)(28)(29)(30). Notably, although the broad antiviral potential of isorhamnetin remains unexplored, a previous study reported its in vitro activity against the influenza virus (37).…”
Section: Resultsmentioning
confidence: 97%
“…Notably, quercetin and kaempferol, as well as their glucoside and rhamnoside derivatives have been shown to possess enhanced antiviral activities against human immunodeficiency virus (HIV) and herpes simplex virus (HSV), genetically close to HBV (21). In line with this finding, the authors have recently reported quercetin and kaempferol, including their derivatives, as well as anthraquinones and catechins with promising anti-HBV activities in cell-culture model (26)(27)(28)(29)(30)(31)(32).…”
Section: Introductionmentioning
confidence: 90%
“…These activities are suggested via direct inhibition of viral products, enhancement of host-immunity or anti-inflammation as well as hepatoprotection from oxidative or apoptotic damages. We have recently demonstrated several plant extracts and bioactive phytoconstituents with promising anti-oxidative, hepatoprotective and anti-HBV activities ( Arbab et al, 2017 , Parvez et al, 2018a , Parvez et al, 2018b , Parvez et al, 2019a , Parvez et al, 2019b , Parvez et al, 2020 , Parvez et al, 2021 ). Natural alkaloids containing nitrogen in a heterocyclic ring have a range of therapeutic salutations, including anti-HBV activities in vitro and in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…EBV lytic reactivation-based therapy is a prevalent treatment for EBV-associated malignancies [ 22 , 38 ]. Two opposing strategies have been applied: one is to induce lytic reactivation of tumor-resident EBV to cytolytic tumor cells [ 39 ], and the other is to prohibit EBV reactivation to relieve cancer progression [ 40 ]. Compared with the former strategy, the latter has the following advantages: (1) inhibition of the EBV lytic cycle decreases the opportunity for EBV reactivation-induced tumorigenesis, (2) blocking EBV lytic production avoids virion transmission to other cells, (3) suppressing EBV reactivation reduces the secretion of oncogenic endocrine factors from EBV-positive tumor cells, and (4) Decreasing lytic protein expression can attenuate the immune evasion of lytic EBV.…”
Section: Discussionmentioning
confidence: 99%